Pengaruh Kualitas Pelayanan dan Lingkungan Fisik Terhadap Kepuasan Konsumen pada Cafe Unsilent Palembang - Novita Damayanti; Muhammad Wadud; Roswaty Roswaty (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
This study aims to investigate the effects of service quality and physical environment on customer satisfaction at the Unsilent Cafe Palembang. Based on the Slovin formula, this study used 99 samples with an accidental technique from a population of 7,710. Data were collected through documentation and questionnaires and analysed using multiple linear regression on SPSS. The results uncover that service quality and physical environment have a positive and significant effect on customer satisfaction. The correlation coefficient (R) of 0.749 proves that service quality and the physical environment have a strong relationship with customer satisfaction. The coefficient of determination (R2) of 0.561 indicates that the contribution of service quality and physical environment explains consumer satisfaction by 56.1%.